2007
DOI: 10.1002/mame.200700111
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Mechanical and Fracture Behavior of Jute‐Fabric‐Reinforced Clay‐Modified Thermoplastic Starch‐Matrix Composites

Abstract: Starch/poly(vinyl alcohol) films plasticized with glycerol were prepared by a solution‐casting method and were used as the matrix material for making jute‐fabric‐reinforced starch‐based composites. Four sets of composites were prepared with a variation in the matrix composition, all having 40 wt.‐% jute fabric as the reinforcement. The mechanical properties were superior in the case of the matrices containing a higher amount of starch. DMA was done to investigate the nature of bonding at the interface. The fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Some enzymatic or chemical modifications of the fibre could be applied to improve the compatibility of these components (Cyras et al, 2008;Ray et al, 2007;Thomas and Atwell, 1997;Zhang and Sun, 2004). These factors were also reported by other researchers.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Some enzymatic or chemical modifications of the fibre could be applied to improve the compatibility of these components (Cyras et al, 2008;Ray et al, 2007;Thomas and Atwell, 1997;Zhang and Sun, 2004). These factors were also reported by other researchers.…”
Section: Resultsmentioning
confidence: 63%
“…Nanocomposites with starch and functional additives exhibited a remarkable improvement in the mechanical properties such as Young modulus and tensile stress (Chen and Evans, 2005;Cyras et al, 2008). Ray et al (2007) reported that jute fabric reinforcement effectively increased the mechanical properties of the starch-based matrix and such composites. Therefore, we can find eco-friendly applications in new fields.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations